Interfacial Engineering over Pt-Calcium Ferrite/2D Carbon Nitride Nanosheet p-n Heterojunctions for Superior Photocatalytic Properties - Singh R.V.; Pai M.R.; Banerjee A.M.; Shrivastava A.; Kumar U.; Sinha I.; Dutta B.; Hassan P.A.; Ningthoujam R.S.; Ghosh R.; Nath S.; Sharma R.K.; Jagannath N.; Bapat R.D. (My University, 2025)
The present study discloses the fabrication of efficient p-n heterojunctions using n-type polymeric bulk carbon nitride (b-CN, Eg = 2.7 eV) or exfoliated nanosheets of carbon nitride (NSCN, Eg = 2.9 eV) with p-type spinel ferrite CaFe2O4 (CFO, Eg = 1.9 eV) for photocatalytic hydrogen generation. A series of p-n combinations were fabricated and characterized by various techniques. The oxide-carbon nitride interactions, light absorption, band alignment at the interface, and water/H3O+ adsorption capability were elucidated over heterojunctions and correlated with the photocatalytic hydrogen yield. The main developments in the present study are as follows: (1) All heterojunctions were more active than pure phases. (2) The photocatalytic activity trend validated an increase in the lifetime of charge carriers from TRPL. Pt(1 wt %)-CFO(1 wt %)/NSCN (481.5 μmol/h/g under ultraviolet (UV)-visible-simulated light, 147.5 μmol/h/g under CFL illumination for 20 h, τavg = 10.33 ns) > Pt-NSCN > Pt-CFO/b-CN > CFO/NSCN > CFO/b-CN > NSCN > Pt/b-CN > mechanical mixture (MM) of 1 wt %CFO + NSCN-MM > 1 wt %CFO + b-CN-MM > CFO > b-CN (τavg = 4.5 ns). (3) Pt-CFO/NSCN was most active and exhibited 250 times enhanced photocatalytic activity as compared to parent bulk carbon nitride, 6.5 times more active than CFO/NSCN, and twice more active than Pt-NSCN. Thus, enhanced activity is attributed to the smooth channelizing of electrons across p-n junctions. (4) NSCN evidently offered improved characteristics as a support and photocatalyst over b-CN. The exfoliated NSCN occupied a superior few-layer morphology with 0.35 nm width as compared to parent b-CN. NSCN allowed 57% dispersion of 6 nm-sized CFO, while b-CN supported 14% dispersion of 7.8 nm-sized CFO particles, as revealed by small-angle X-ray scattering spectroscopy (SAXS). Sizes of 2-4 nm were observed for Pt nanoparticles in the 1 wt %Pt/1 wt % CFO/NSCN sample. A binding energy shift and an increase in the FWHM of X-ray photoelectron spectroscopy (XPS) core level peaks established charge transfer and enhanced band bending on p-n contact in Pt-CFO/NSCN. FsTAS revealed the decay of photogenerated electrons via trapping in shallow traps (τ1, τ2) and deep traps (τ3). Lifetimes τ1 (3.19 ps, 42%) and τ2 (187 ps, 31%) were higher in NSCN than those in b-CN (τ1 = 2.2 ps, 42%, τ2 = 30 ps, 31%), which verified that the recombination reaction rate was suppressed by 6 times in NSCN (k2 = 0.53 × 1010 s-1) as compared to b-CN (k2 = 3.33 × 1010 s-1). Deep traps lie below the H+/H2 reduction potential; thus, electrons in deep traps are not available for photocatalytic H2 generation. (5) The role of CFO in enhancing water adsorption capability was modeled by molecular dynamics. NSCN or b-CN both showed very poor interaction with water molecules; however, the CFO cluster adsorbed H3O+ ions very strongly through the electrostatic interaction between calcium and oxygen (of H3O+). Pt also showed a strong affinity for H2O but not for H3O+. Thus, both CFO and Pt facilitated NSCN to access water molecules, and CFO further sustained the adsorption of H3O+ molecules, crucial for the photocatalytic reduction of water molecules. (6) Band potentials of CFO and NSCN aligned suitably at the interface of CFO/NSCN, resulting in a type-II band structure. Valence band offset (VBO, ΔEVB) and conduction band offset (CBO, ΔECB) were calculated at the interface, resulting in an effective band gap of 1.41 eV (2.9 - ΔEVB = 1.9 - ΔECB), much lower than parent compounds. The interfacial band structure was efficient in driving photogenerated electrons from the CB of CFO to the CB of NSCN and holes from the VB of NSCN to the VB of CFO, thus successfully separating charge carriers, as supported by the increased lifetime of charge carriers and favorable photocatalytic H2 yield. © 2024 The Authors. Published by American Chemical Society.